(untitled) (Research, Society and Development, 2022)
Teaching Mathematics is a challenge for teachers, especially in elementary school. It is very common to see unmotivated students. In this scenario of limiting the evolution of indicators, as a consequence, there are increases in repetition rates. Thus, it is important to discuss the need for new educational methodologies. This study aims to analyze what impacts the adoption of gamification can have on the performance of elementary school students in Mathematics. The research has a bibliographic character, and the survey consisted of consulting scientific articles published in the last ten years.. The results indicate that gamification enables the construction of knowledge in the short term, the increase in the quality of teaching and the reduction of school dropout. Gamification is an excellent tool to increase students’ interest in mathematics.